The Effect of Changes in Long-Term Liabilities on Share Price of PT Jasa Marga (Persero) Tbk - Pranoto, Madeline Guenevere; Maratno, Sylvia Fettry Elvira (Universitas Mohammad Husni Thamrin, 2025)
This study aims to examine the effect of long-term liabilities on the stock price of PT Jasa Marga (Persero) Tbk using the company’s financial data. As an infrastructure company operating toll road networks, PT Jasa Marga requires substantial long-term financing to support the development and maintenance of its assets. Long-term liabilities serve as a major funding source; however, an increase in these liabilities may raise financial risk, which in turn can affect investor perception and stock price movements. This research uses data on long-term liabilities and stock prices of PT Jasa Marga (Persero) Tbk for the period 2017–2024, with a total of 30 observations. The data were analyzed using a simple linear regression method to examine the relationship between long-term liabilities as the independent variable and stock price as the dependent variable. The results show that long-term liabilities have a negative but statistically insignificant effect on the stock price. This is indicated by a regression coefficient of –2.30764 × 10⁻⁸ and a p-value of 0.0577, which is higher than the 0.05 significance level. Furthermore, the R Square value of 0.1227 indicates that only 12.27% of the variation in the stock price of PT Jasa Marga (Persero) Tbk can be explained by changes in long-term liabilities, while the remaining variation is influenced by other factors such as macroeconomic conditions, government policies in the infrastructure sector, operational performance, and market sentiment. Thus, this study indicates that although long-term liabilities have a negative directional relationship with the stock price, their impact is not statistically strong. Therefore, changes in the stock price of PT Jasa Marga (Persero) Tbk are more strongly influenced by external and other fundamental factors beyond the company’s long-term liability structure.